Frontal ﬁbrosing alopecia development in two patients after botulinum toxin applications: relationship or coincidence? - Mariana Abdo de Almeida; Michele Maria Reis-Feroldi; Marcia Lanzoni Alvarenga Lira (Sociedade Brasileira de Dermatologia (SBD), 2021)
Frontal fibrous alopecia is a primary lymphocytic scarring alopecia that is difficult to control, with a perifollicular lichenoid infiltrate marking its histology. Since its description in 1994 by Kossard, there has been an increase in cases reported worldwide. This article reports two cases that underwent incisional biopsies with longitudinal and transverse sections in areas presenting higher disease activity and reviews some aspects of this dermatosis. It also addresses the suspicion of a possible relationship with the application of botulinum toxin - a question already raised by other authors but with no established confirmation.